Nasobiliary Drainage - Paul Kortan (Canadian Journal of Gastroenterology)
Placement of nasobiliary tubes has now become a widely accepted method for therapeutic drainage and instillation of solvents into the biliary tree. The author routinely uses a 300 cm long, 7 or 10 French, specially performed Teflon catheter, which adapts to the anatomy of the duodenum and bile ducts, for the following indications: decompression of obstructed bile duct in acute suppurative cholangitis; prevention of stone impaction after endoscopic sphincterotomy; sequential cholangiography; biliary fistula; instillation of solvents for common bile duct scones; local radiotherapy of biliary malignancies; aspiration of bile for chemical and bacteriological studies; and drainage of pancreatic pseudocysts. Pancreatic or biliary drains should supplement traditional diagnostic and therapeutic modalities in patients with surgical or medical lesions of the pancreas and biliary tree.